Understanding the molecular mechanism of leaf morphogenesis in vegetable crops conduces to breeding process - Hao, Ning; Cao, Jiajian; Wang, Chunhua; Zhu, Yipeng; Du, Yalin; Wu, Tao (Frontiers in Plant Science, 2022)
Leaf morphology can affect the development and yield of plants by regulating plant architecture and photosynthesis. Several factors can determine the final leaf morphology, including the leaf complexity, size, shape and margin type, which suggests that the leaf morphogenesis is a complex regulation network. Basically, the formation of diverse leaf morphology is precisely controlled by genes regulation on translation and transcription level. To further reveal that, more and more genome data has been published in kinds of vegetable crops and advanced genotyping approaches are also applied to identify the causal gene for the target traits. Therefore, the studies on the molecular regulation of leaf morphogenesis in vegetable crops have also been largely improved. This review will summarize the progress on identified genes or regulatory mechanism of leaf morphogenesis and development in vegetable crops. These identified markers can be applied for further molecular assisted selection (MAS) in vegetable crops. Overall, the review will contribute to understanding the leaf morphology of different crops from the perspective of molecular regulation and shortening the breeding cycle for vegetable crops